Accountability for village financial management: Clarity of budget targets and competency of village financial management officials - Indrijawati, Aini; Darmawati,; Anwar, Fithyani; Fatmawati,; Samsinar, (Asian Development Policy Review, 2024)
This study examines how community participation, clarity of budget targets and the competence of village officials impact village financial accountability. Understanding these factors is crucial for enhancing financial performance, reducing corruption risks and ensuring effective and efficient budget utilization in villages. This research adopts a quantitative approach with an associative design to explore causal relationships among variables. Multiple linear regression was used for data analysis. The findings indicate a significant impact of community participation, clarity of budget targets and official competence on village financial accountability. The results reveal that these factors significantly influence financial accountability in rural areas. The researcher suggests that future studies delve deeper into external factors affecting village fund management accountability. Enhancing the clarity of budget targets and the competence of village officials is crucial for significantly impacting village fund management. This research contributes to the global discourse by identifying key factors influencing financial accountability at the village level. It underscores the importance of community participation, clarity of budget targets and the competence of village officials. The study's findings can guide countries to enhance village financial performance, mitigate corruption risks and ensure effective and efficient use of village level budgets ultimately promoting public welfare.